Les ambiances dans les récits de visite : une source pour l’étude de la réception de l’architecture - Julien Bastoen (Ambiances)
This paper considers museum visitor reviews neither in terms of aesthetic experience nor from a sociological point of view, but rather as a source of architectural history and the reception theory of architecture. As they deal with narratives on atmosphere (accessibility, flow, comfort, lightning, climate, etc.), visitor reviews published in general-interest newspapers or art and architecture journals address or reveal architectural issues that might have been underestimated and overlooked during the design process. The case of the new Luxembourg Museum building in Paris, inaugurated in 1886, is symptomatic of how the inconsistent policy of the French state regarding contemporary art affected the museum’s design and atmosphere, as well as topics of preventive conservation.